Literature Review: Hubungan Durasi dan Kualitas Tidur dengan Masalah Perilaku Emosional pada Anak Usia 3–6 Tahun - Khansa Aulia Putri; Handajany, Sofie (Journal of Educational Innovation and Public Health, 2026)
Sleep duration and sleep quality are essential physiological needs that play a significant role in the emotional and behavioral development of children aged 3–6 years. Adequate sleep supports brain development, cognitive functioning, emotional regulation, and social interaction skills in early childhood. Conversely, poor sleep duration and low sleep quality may negatively affect children’s attention, mood stability, and ability to interact socially with peers and caregivers. This article is a literature review using a systematic review approach that analyzes 10 scientific articles published between 2016–2026 to evaluate the relationship between sleep duration and sleep quality with emotional and behavioral problems in preschool children. The article selection process followed the PRISMA flow diagram, with articles sourced from Google Scholar, PubMed, and ScienceDirect databases. The findings consistently indicate that inadequate sleep duration and poor sleep quality are associated with increased emotional and behavioral problems, including hyperactivity, anxiety, emotional dysregulation, and difficulties in social interaction among children. Furthermore, sleep disturbances were found to negatively influence children’s emotional self-regulation abilities, which are crucial for adaptive behavior. Therefore, ensuring adequate sleep duration and improving sleep quality are important strategies to support optimal emotional and behavioral development in preschool-aged children.